Reaksi pemimpin dan masyarakat terhadap bantuan prihatin nasional - Azizan, Intan Syahriza; Ismail, Junaida (Universiti Teknologi MARA, Kedah, 2023)
Bantuan Prihatin Nasional (BPN) is a financial aid channeled by the government to help Malaysians who are affected by the COVID-19 pandemic that is sweeping the world. This is one of the assistances provided by the government in ‘Pakej Rangsangan Ekonomi Prihatin Rakyat’ which is given on a one-off basis to the B40 and M40 groups. Controls have been made in curbing this epidemic to be spread by implementating the Movement Control Order (MCO) to contain and control the rate of infection from continuing to increase. Therefore, people are encouraged to stay at home and reduce interactions with outsiders. This causes many companies to be unable to operate as usual and suffer losses. Some even had to be temporarily closed or continue to cause many to lose their jobs and sources of income. This situation at once caused the collapse of the economic system as a whole. Concerned about this situation, YAB Prime Minister has announced that RM5.63 billion in the first phase will be allocated to 8.3 million households and single individuals. Looking at many who are deeply affected by the threat that has hit the world in early 2020 which has cause the world economy to be severely affected and the socioeconomic situation to be compromised, the government takes the approach of channeling aid in various forms. This will be able to determine the satisfaction of the people and the progress of the country to be continued as usual. Therefore, this assistance should be well received by all levels of society. In line with the aspirations of our Prime Minister, this paper aims to review and identify the reaction of Malaysian leaders and the public towards BPN in ensuring the economic survival of the people and the country in order to assist the government in improving or increasing efforts to improve the economic standards of the people and the country that have been affected by this COVID-19 pandemic.